Pengaruh Mata Kuliah Pengembangan Media Pembelajaran Ekonomi terhadap Kreativitas Mahasiswa Sebagai Pre-Service Teacher: Studi Empiris pada Mahasiswa Pendidikan Ekonomi Universitas Sriwijaya - Arini Nasihah; Ikbal Barlian (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to determine the influence of the Economic Learning Media Development course on students' creativity as pre-service teachers in the Economic Education Study Program at Sriwijaya University, class of 2022. This research employs a quantitative approach with a causal associative method. Data collection techniques include questionnaires and interviews, with validity testing using the product-moment correlation and reliability testing using Cronbach's alpha formula. Data analysis includes normality tests, linearity tests, and hypothesis testing using simple regression analysis and the coefficient of determination. The results indicate that the Economic Learning Media Development course significantly influences students' creativity as pre-service teachers, with F_calculated ≥ F_table (61.544 ≥ 3.94), leading to the rejection of H₀ and acceptance of Hₐ. The obtained regression equation is Y = 35.424 + 0.679X, meaning that each one-point increase in variable X will increase variable Y by 0.679. The coefficient of determination is 40.34%, indicating that this course contributes to students' creativity, while 59.66% is influenced by other factors.